The Hepatotoxicity of Antifungal Medications in Bone Marrow Transplant Recipients - Fischer, Michael A.; Winkelmayer, Wolfgang C.; Rubin, Robert H.; Avorn, Jerry (Clinical infectious diseases, 2005)
Background. Systemic antifungal medications can be lifesaving but can also have important toxicities. With a number of new antifungal drugs being introduced, there is a compelling need to define the toxicities associated with existing therapies. Methods. We identified cases of hepatotoxicity among patients who underwent bone marrow transplantation and selected matched control subjects from the same population. Multivariable logistic regression modeling was used to control for patient characteristics in evaluating the relationship between hepatotoxicity and exposure to antifungal medications. Follow-up analyses were performed for patients who continued receiving antifungal medications after developing hepatotoxicity. Results. The unadjusted incidence of hepatotoxicity was 0.78 cases per 100 patient-days of exposure to amphotericin deoxycholate, 0.98 for fluconazole, and 1.50 for liposomal amphotericin B. Case-control analyses found that liposomal amphotericin B was associated with a substantial increase in the risk of hepatotoxicity in these patients (odds ratio [OR], 3.33; 95% confidence interval [CI], 1.61–6.88); a smaller increase in risk was found for fluconazole (OR, 1.99; 95% CI, 1.21–3.26). There was no statistically significant association between amphotericin B deoxycholate and the development of hepatotoxicity. Patients had greater elevations of serum transaminase values associated with exposure to larger cumulative doses of liposomal amphotericin B. In the follow-up analysis of patients who developed hepatotoxicity and who continued receiving antifungal medication, one-third of those receiving liposomal amphotericin B had marked increases in bilirubin levels, as opposed to 8% of patients treated with fluconazole. Conclusions. In these bone marrow transplant recipients, liposomal amphotericin B and fluconazole were both associated with increased risk of hepatotoxicity, independent of other treatments received or patient characteristics; the magnitude of the risk was larger for liposomal amphotericin B. Patients who develop hepatotoxicity appear to tolerate continued therapy with fluconazole, but a large fraction of those who received liposomal amphotericin B have worsening conditions with continued treatment.